Social inequalities in traditional and emerging screen devices among Portuguese children: a cross-sectional study - Rodrigues, Daniela (2020)
Background: Children are often exposed to too much screen time but few studies have explored the use of old and new digital media among young children. This study assesses screen time, including traditional and mobile devices, in pre-school and elementary school-aged children, according to their gender, age, and socioeconomic position (SEP). Methods: A total of 8430 children (3 to 10 years; 50.8% boys) from the north, center and south-central Portugal were included in the present study. Data was collected by a parental questionnaire during 2016/2017. Children’s screen time (by media device, weekdays and at the weekend; calculated by mean minutes per day) were reported by parents. Analysis were carried to compare screen time by children’s age, gender and family SEP (classified using father’s educational degree). Results: Daily screen time was high both in children aged 3 to 5 and 6 to 10 years – 154 min/day (95% CI: 149.51– 158.91) and 200.79 min/day (95% CI: 197.08–204.50), respectively – and the majority of children, independently of their gender, exceed the recommended 2 h/day of screen viewing. Children are still primarily engaging in screen time through television but the use of mobile devices, particularly tablets, were already high among 3 year-old children and increased with age. SEP was a negative predictor of screen time in the linear regression analysis, including after adjustment. Conclusions: Considering the negative health impacts of excessive screen time, recognizing subgroups at risk of excessive screen time and identifying how each device is used according to age is fundamental to enable appropriate future interventions. The screen time in children aged 3–10 years is longer than the recommended, particularly among boys and in those children from lower SEP. Parents and policymakers should have in mind that children spend most of their screen time watching television but mobile devices are becoming extremely popular starting at a young age.